Computer diagnostic of cardiovascular system development experience and prospects - Zelensky, A.; Sharonov, V.; Shulgin, V. (Видавництво Львівської політехніки, 2010)
The paper addresses a number of problems solved in the design of computer systems for functional diagnostics, in particular - the synthesis and restoration of electrocardiographic leads, fetal electrocardiogram separation and analysis during abdominal cardiography, the development of telemedicine and personal diagnostic devices.
Keywords: functional diagnosis; electrocardiography; leads transformation; fetal ECG; KhAI-Medica